(untitled) (CAHIERS MAGELLANES-NS, 2024)
The main objective of this study is to Understanding The Security Awareness On Using Digital Banking Service and the challenges faced. The data were collected through well-structured questionnaires which contain closed end question. The digital banking increases the growth of the country, moving faster, widely accepted and reduces time consumption. This survey is collected from general public residing in Chennai. The research design used for this study is descriptive in nature and Convenience sampling is used for the purpose of collecting data from the respondents in this research. It includes survey and fact- findings enquire of different kinds. The methods of data collection for the study include both primary and secondary data .A sample data of 152 respondents helped to analyze the challenges faced by digital banking users in Chennai and understand the various issues in digital banking usage .The statistical tool used for analyzing and interpreting the opinions of the users that include simple percentage analysis and hypothesis testing (chi square ,regression test).It is found that irrespective of gender respondents were aware about using digital banking services safely. However, it is necessary being an effective product of banking operations it comes with few technical and non-technical issues that needs to be addressed by authorities.